DRAW ME A PROVERB: ENHANCING WRITING SKILLS THROUGH WISDOM - Dwi Haryanti (Universitas Ahmad Dahlan)
Proverbs are believed to have an important role in language teaching as a part of obtaining cultural knowledge, metaphorical understanding, and communicative competence. They have been considered an important part of the fostering of pupils, as they prompt moral values and present common behavior. In 2013 curriculum enacted for senior high school students in Indonesia, the proverb is one of the main materials studied in English subject. This paper aims at presenting how transforming proverbs to pictures and paragraph provides alternative method to help the students understand the meaning as well as to enhance their writing skills. To do this aim, three general phases were applied, namely before the instruction phase, during the instruction phase, and after the instruction phase. The result shows that transforming proverbs to pictures and paragraphs helps the students to convey the culture and wisdom. Moreover, it provides students with a rich source of vocabulary. It also gives them an opportunity of making comparisons between their own proverbs and the English ones, thus broadening their knowledge of the world. Finally, it helps students to write in English in a more natural, native-like way using the fixed expression.